Meta-analytic evidence for decreased heart rate variability in chronic pain implicating parasympathetic nervous system dysregulation - Tracy, Lincoln M.; Ioannou, Liane; Baker, Katharine S.; Gibson, Stephen J.; Georgiou-Karistianis, Nellie; Giummarra, Melita J. (Pain (Amsterdam), 2016)
Both sympathetic and parasympathetic nervous systems are involved in regulating pain states. The activity of these systems seems to become disturbed in states of chronic pain. This disruption in autonomic balance can be measured through the assessment of heart rate variability (HRV), that is, the variability of the interval between consecutive heart beats. However, there is yet to be a systematic evaluation of the body of literature concerning HRV across several chronic pain conditions. Moreover, modern meta-analytical techniques have never been used to validate and consolidate the extent to which HRV may be decreased in chronic pain. Following the preferred reporting items for systematic reviews and meta-analyses (PRISMA) statement guidelines, this study systematically evaluated and critically appraised the literature concerning HRV in people living with chronic pain. After screening 17,350 sources, 51 studies evaluating HRV in a chronic pain group met the inclusion criteria. Twenty-six moderate-high quality studies were included in quantitative meta-analyses. On average, the quality of studies was moderate. There were 6 frequency-domain and time-domain measures of HRV across a broad range of chronic pain conditions. High heterogeneity aside, pooled results from the meta-analyses reflected a consistent, moderate-to-large effect of decreased high-frequency HRV in chronic pain, implicating a decrease in parasympathetic activation. These effects were heavily influenced by fibromyalgia studies. Future research would benefit from wider use of standardised definitions of measurement, and also investigating the synergistic changes in pain state and HRV throughout the development and implementation of mechanism-based treatments for chronic pain.